Binding of chloroplast signal recognition particle to a thylakoid membrane protein substrate in aqueous solution and delineation of the cpSRP43-substrate interaction domain - Cain, Peter; Holdermann, Iris Valerie; Sinning, Irmgard; Johnson, Arthur E.; Robinson, Colin (Biochemical journal, 2011)
A cpSRP [chloroplast SRP (signal recognition particle)] comprising cpSRP54 and cpSRP43 subunits mediates the insertion of light-harvesting proteins into the thylakoid membrane. We dissected its interaction with a full-length membrane protein substrate in aqueous solution by insertion of site-specific photo-activatable cross-linkers into in vitro-synthesized Lhcb1 (major light-harvesting chlorophyll-binding protein of photosystem II). We show that Lhcb1 residues 166-176 cross-link specifically to the cpSRP43 subunit. Some cross-link positions within Lhcb1 are in the ‘L18’ peptide required for targeting of cpSRP substrates, whereas other cross-linking positions define a new targeting signal in the third transmembrane span. Lhcb1 was not found to cross-link to cpSRP54 at any position, and cross-linking to cpSRP43 is unaffected by the absence of cpSRP54. cpSRP43 thus effectively binds substrates autonomously, and its ability to independently bind an extended 20+-residue substrate region highlights a major difference with other SRP types where the SRP54 subunit binds to hydrophobic target sequences. The results also show that cpSRP43 can bind to a hydrophobic, three-membrane span, substrate in aqueous solution, presumably reflecting a role for cpSRP in the chloroplast stroma. This mode of action, and the specificity of the cpSRP43-substrate interaction, may be associated with cpSRP's unique post-translational mode of action.
Im Titel ist die Zahl 43 tiefgestellt
Gesehen am 27.06.2022